Management Performance Model of Senior High School Teachers of Muhammadiyah In South Sumatera - Rulitawati Rulitawati; Ahmad Husein Ritonga; Lias Hasibuan (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This research aimed at analyzing school management which manages teachers’ management model that impacts the performance of High School teachers of Muhammadiyah in South-Sumatera Province. This field research applied a descriptive-qualitative approach. The technique for collecting the data was through observation, interview and documentation. The research subjects selected by using purposive sampling technique. The technique for analyzing the data was through data analysis by reducing, presenting, verifying and drawing conclusions, and also using reliable and extended participation techniques, careful observation, triangulation and consulting with advisors. The results showed that management performance model in Senior High School of Muhammadiyah was a successful management model which enables to improve teachers’ performance. The success of applying this model can be regarded on management performance model of teachers in line with POAC management, in which POAC was implemented to meet teachers’ success, and also other factors, such as humans’ competency and motivation in managing teachers’ performance, the effectiveness of managing performance starting from input, process and teachers’ performance objective, as well as the use of facilities and infrastructure, time, finance (capital) had supported the success of teacher's performance.